Network functional connectivity analysis in individuals at ultrahigh risk for psychosis and patients with schizophrenia - Chen, Xiongying; Li, Xianbin; Yan, Tongjun; Dong, Qianhong; Mao, Zhen; Wang, Yanyan; Yang, Ningbo; Zhang, Qiumei; Zhao, Wan; Zhai, Jinguo; Chen, Min; Du, Boqi; et al. (Psychiatry research. Neuroimaging, 2019)
•UHR subjects are promising candidate of identifying biomarkers for schizophrenia.•FDC is an unbiased method to examine voxelwise whole-brain functional connectivity.•UHR subjects and schizophrenia patients showed FDC abnormalities.•Abnormalities included increased FDC in the MPFC and reduced FDC in the right FG.•These abnormalities also correlated with their disorganization symptoms. Schizophrenia is a severe mental disorder, and the onset of which is preceded by a stage of ultrahigh risk (UHR) for developing psychosis. Therefore, analyzing individuals with UHR is essential for identifying predictive biomarkers for the onset of schizophrenia. The current study aimed to identify such biomarkers based on a voxelwise whole-brain functional degree centrality (FDC) analysis. Conjunction analysis showed that, compared with healthy controls, both UHR subjects and patients with schizophrenia showed significantly increased FDC at the medial prefrontal cortex (MPFC) and significantly decreased FDC at the right fusiform gyrus (FG). The subsequent partial correlation analysis showed significant correlations between the disorganization symptoms and FDCs at the MPFC and the right FG for both UHR subjects and patients with schizophrenia. These findings suggest that FDC within the MPFC and the right FG could be candidate biomarkers for the onset of schizophrenia.